Work-Related Musculoskeletal Symptoms Among Rattan Craft Workers: A Cross-Sectional Ergonomic Assessment - Mukhammad Al - Yusni; Khoirul Muslim (Journal of Research in Industrial Engineering and Management, 2026)
Work-related musculoskeletal disorders (WMSDs) represent a significant occupational health burden in labor-intensive industries, particularly in traditional craft sectors. Despite the economic importance of Indonesia’s rattan craft industry, no systematic investigation of ergonomic risks and musculoskeletal health outcomes among rattan workers has been conducted. This study aimed to assess the prevalence of WMSDs symptoms, identify task-specific ergonomic risk factors, and propose targeted interventions to improve working conditions in the rattan craft industry. A cross-sectional study was conducted among 100 workers across eight rattan craft workshops in Cirebon Regency, Indonesia. Ergonomic risk assessment was performed using Indonesia’s SNI 9011:2021 standard, incorporating postural analysis, workstation measurements, task timing, and environmental monitoring. WMSDs symptoms were assessed using a modified questionnaire adapted from SNI 9011:2021. Chi-square tests examined associations between individual and work-related factors and symptom severity. High prevalence rates of WMSDs symptoms were documented including 66% for lower back, 63% for hands, and 51% for shoulders. Task-specific risk scores ranged from 13 to 19.5, with steaming tasks receiving the highest score (19.5) due to prolonged standing (75.49% of workday), extreme forward bending (37.6° neck flexion, 32.8° torso flexion), and heat exposure (34.45°C). Binding tasks caused severe shoulder complaints in 81.5% of workers due to sustained overhead arm activity. Significant associations were found between symptoms and smoking status (hands: p=0.049; lower back: p=0.037), gender (shoulders: p<0.001), and workstation design. Rattan craft workers experience high rates of musculoskeletal symptoms comparable to the highest reported in traditional craft literature. Task-specific ergonomic hazards, particularly prolonged standing and extreme postural demands in steaming and binding tasks, require urgent intervention. Recommendations include workstation redesign to accommodate anthropometric diversity, introduction of mechanical assists for high-force tasks, environmental controls for heat and lighting, and integration of smoking cessation programs with ergonomic improvements.